2001
DOI: 10.1128/aem.67.8.3756-3758.2001
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Streptococcus iniae from Diseased Fish Previously Vaccinated with a Streptococcus Vaccine

Abstract: Streptococcus iniae was recovered from diseased rainbow trout (Oncorhynchus mykiss, Walbaum) previously vaccinated against streptococcosis. PCR and serological methods indicate the presence of a new serotype in the diseased fish.The fish pathogen Streptococcus iniae (11) is endemic in various parts of the world, including Israel (6) and North America (10). S. iniae infection of rainbow trout (Oncorhynchus mykiss) produces a disease which substantially affects the brain, with only minor pathological changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 17 publications
1
62
1
Order By: Relevance
“…Strain replacement in response to continuous immunisation selective pressure has been reported for other fish pathogens (Bachrach et al 2001) and medically important bacteria (e.g. Urwin et al 1996, Spratt & Greenwood 2000, Hallander et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Strain replacement in response to continuous immunisation selective pressure has been reported for other fish pathogens (Bachrach et al 2001) and medically important bacteria (e.g. Urwin et al 1996, Spratt & Greenwood 2000, Hallander et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports concerning the diversity of S. iniae strains in biochemical characteristics (Pier et al, 1978;Sakai et al, 1993;Stoffregen et al, 1996;Dodson et al, 1999), genomic structure (Eldar et al, 1997;Fuller et al, 2001) and serological properties (Pier et al, 1978;Klesius et al, 2000;Bachrach et al, 2001;Barnes et al, 2003). In the present study, though genomics were not investigated, the two serological types were indistinguishable by any biochemical tests performed.…”
Section: Discussionmentioning
confidence: 38%
“…However, for S. iniae this has scarcely been conducted so far, except that Pier et al (1978) demonstrated group and strain-specific antigens in cellextracts and that Eldar et al (1997) investigated the antigen recognition by sera of vaccinated fish. Recently Bachrach et al (2001) and Barnes et al (2003) reported the second serotype of S. iniae derived from diseased fish in Israel and USA.…”
mentioning
confidence: 99%
“…There are 2 serotypes of Streptococcus iniae. A previous study has shown that infection with serotype I S. iniae tends mainly to cause neural lesions, while infection with serotype II S. iniae predominately induces systemic inflammation, affecting multiple organs with diffuse internal haemorrhages (Bachrach et al 2001). We found that the S. iniae-infected channel catfish displayed systemic inflammation, which suggests that the pathogen is likely to be serotype II of S. iniae.…”
Section: Discussionmentioning
confidence: 54%